Cyklosporin A v terapii psoriázy a atopického ekzému - Novotný, František (Československá dermatologie, 1999)
Cyclosporin A was used in the treatment of 42 psoriatic patients and 13 subjects with a severe chronic state atopic eczema. The doses ranged from 2.5 to 5 mg/kg/day for a period of three months. eczema the condition improved on averacre bv 82 %. Undesirable side.effects were minimal and reversible. In the prevention of relanses denondincř on the natients. intermittent or continual reversible. In the prevention of relapses, depending on the patients, intermittent or continual cyclosporin A treatment proved useful. Some patients were changed to rotational treatment using other preparations or to balneophototherapy incl. prevention focused on trigger mechanisms. Cyclosporin A is considered a great asset in the treatment of severe autoimmune dermatoses.
Keywords: recidiva; dospělí; atopická dermatitida; předškolní dítě; psoriáza; Adolescent; cyklosporin; sekundární prevence; Female; Cyclosporine; dítě; mužské pohlaví; lidé; Recurrence; Secondary Prevention; Child, Preschool; Dermatitis, Atopic; Child; ženské pohlaví; Psoriasis; Humans; Male; Adult; mladiství